SOCIAL MEDIA ADDICTION, WORK TECHNOLOGY CONFLICTS ON TASK PERFORMANCE IN ISLAMIC STUDENTS - Mardiah, Anisatul; Melisa Paulina; Tri Handayani; Arung Samudra; Sari Emilia; Triana Aprilia; Siti Miyanti Juniar; Anisatul Mardiah (Psikis : Jurnal Psikologi Islami, 2024)
Challenges associated with social media use, such as distractions and reduced focus on academic activities, can negatively impact students’ task performance. This research aimed to analyze the impact of social media addiction, work technology conflicts, and demographic variables (gender and age) on Islamic students’ task performance. The research used a quantitative and cross-sectional design approach involving 184 Islamic students. Data were collected using validated scales such as Task Performance, Social Media Addiction, and Work-Technology Conflict scales. Data analysis was carried out using multiple linear regression and confirmatory factor analysis. The results showed that social media addiction and demographic variables did not significantly impacted students’ task performance. However, work-technology conflict has a significant negative effect on task performance. Work-technology conflict levels were associated with a decrease in student task performance. In addition, the analysis showed that the proportion of social media addiction variables, work-technology conflict, gender, and age together influencing task performance was 11.8%, with the remaining 88.2% influenced by other variables outside the research. This showed that students who experienced difficulty in managing the use of technology for academic activities may experience a decrease in productivity. Therefore, educational institutions or campuses can develop programs or strategies to help students manage work-technology conflicts, for example by providing education about time management and techniques for efficient use of technology so as not to interfere with academic focus. With these implications, it is hoped that the research results can be a basis for universities or other educational institutions in designing programs and policies that support the optimization of student academic achievement, especially in facing the challenges of technology and social media. By understanding washatiyah, Islamic students can use social media wisely without becoming addicted, which could negatively impact their task performance